Truth and falsehood in the history of the Great Patriotic War - Kanzay, Aldyn-ool K. (The New Research of Tuva, 2010)
Article is composed of the text of author’s report on round table “Victory of Soviet people over the fascist Germany is a victory of Tuvan people as well”, that took place on April 30, 2010 at the Tuvan Institute for Humanitarian Researches marking the 65th anniversary of the Great Victory.
Keywords: Great Patriotic War; history; USSR; truth; falsehood; diplomacy; losses; Tuvan People; People’s Republic of Tuva; Tuva